Simulation of the magnetic coupling phenomena in electric vehicle wireless charging. Issue 16 (17th December 2018) - Zheng, Zhong; Song, Ruya; Huang, Xiaohua; Xu, Jinxing; Gao, Chao
Abstract : In recent years, wireless charging technology for electric vehicles has aroused widespread concern in the industry. The technology has the advantages of flexibility and convenience, safe operation and low maintenance cost, and is one of the development trends of charging and discharging technology for electric vehicles in the future. The author summarises the current research status from the most crucial aspects of the magnetic coupling structure of wireless charging systems of electric vehicles, which are the transmission coil structure and the resonance compensation network. Finally, the author put forward the urgent problem to be solved at present is the interoperation problem of the magnetic coupling mechanism in different technical routes. Finally, a magnetic field analysis model based on finite element calculation is established, which provides a tool for the interoperability research of magnetic coupling mechanism.